2010
DOI: 10.1093/protein/gzq022
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical determinants of soluble intrabody expression in mammalian cell cytoplasm

Abstract: Soluble antibody fragments are desirable not only as potential therapeutic and diagnostic agents for extracellular targets but also as 'intrabodies' for functional genomics, proteomics and gene therapy inside cells. However, antibody fragments are notoriously aggregation-prone when expressed intracellularly, due in part to unfavorable redox potential and macromolecular crowding in cell cytoplasm. Only a small proportion of intrabodies are soluble in cytoplasm and little is known about the sequence determinants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 83 publications
6
59
0
Order By: Relevance
“…3 However, many promising intrabodies suffer from reduced cytoplasmic solubility, 4 and are aggregation-prone due to the intracellular redox potential and macromolecular crowding. [5][6][7] Such aggregationprone intrabodies may in fact exacerbate the proteostatic burden in proteinopathies such as Parkinson disease (PD). Currently, Intrabodies can be powerful reagents to effect modulation of aberrant intracellular proteins that underlie a range of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, many promising intrabodies suffer from reduced cytoplasmic solubility, 4 and are aggregation-prone due to the intracellular redox potential and macromolecular crowding. [5][6][7] Such aggregationprone intrabodies may in fact exacerbate the proteostatic burden in proteinopathies such as Parkinson disease (PD). Currently, Intrabodies can be powerful reagents to effect modulation of aberrant intracellular proteins that underlie a range of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this result the nuclear version of 353scFv also tends to aggregate and localizes in the cytoplasmic compartment of transfected cells, despite the presence of a dominant NLS signal, leading to co-aggregation of HP1β in the cytoplasm (data not shown). As reported for other intrabodies, the intrinsic insolubility of cyt-353 scFv in the cytoplasm might be related to its net overall charge and/or hydropathicity [50]. Control experiments showing that another insoluble scFv does not lead to HP1β aggregation suggest that even though the intrabody folding kinetics are suboptimal, there is still enough of a binding site present that the effect appears to be specific, although direct evidence of this mechanism is still lacking.…”
Section: Discussionmentioning
confidence: 89%
“…[39][40][41][42][43][44] Mutation of 3 residues in CDR3 of LL3 was sufficient to disrupt antigen binding; this was in line with another intracellular domain antibody study where mutation of 4 residues in CDR1 was sufficient to disrupt intracellular function. 29 A number of studies have investigated the effect of intracellular antibody pI on intracellular aggregation, 45 and concluded that an overall negative charge at pH7.4 was beneficial to intracellular antibody solubility. Consistent with this work the intracellular antibody LL3 studied here was predicted to have a pI value of 6.7.…”
Section: Discussionmentioning
confidence: 99%